2021
DOI: 10.3390/ijms22115578
|View full text |Cite
|
Sign up to set email alerts
|

Sophisticated Conversations between Chromatin and Chromatin Remodelers, and Dissonances in Cancer

Abstract: The establishment and maintenance of genome packaging into chromatin contribute to define specific cellular identity and function. Dynamic regulation of chromatin organization and nucleosome positioning are critical to all DNA transactions—in particular, the regulation of gene expression—and involve the cooperative action of sequence-specific DNA-binding factors, histone modifying enzymes, and remodelers. Remodelers are molecular machines that generate various chromatin landscapes, adjust nucleosome positionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 319 publications
(439 reference statements)
3
25
0
21
Order By: Relevance
“…Relatedly, it was recently shown that SHL2 can harbor nonspecific protein binding, as revealed by the TATA-box-binding-protein:SHL2 complex (65). At the SHL2 H3 α3and H4 α2-helices form very few protein contacts, providing an extra flexibility to this region (66)(67)(68)(69). All in all, it is clear that weak histone-DNA interactions at SHL2 makes SHL2 a good recognition site for Sox.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, it was recently shown that SHL2 can harbor nonspecific protein binding, as revealed by the TATA-box-binding-protein:SHL2 complex (65). At the SHL2 H3 α3and H4 α2-helices form very few protein contacts, providing an extra flexibility to this region (66)(67)(68)(69). All in all, it is clear that weak histone-DNA interactions at SHL2 makes SHL2 a good recognition site for Sox.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin dynamics rely mainly on posttranslational modifications (PTMs), nucleosome positioning and spatial genome organization; these modifications are involved in complex crosstalk with DNA methylation [ 56 ]. Currently, there is no clinical proof that such epigenetic modifications can directly lead to HRD in the context of OC [ 57 ]. However, as chromatin can act as a gene silencer and a barrier to efficient DNA repair, it appears plausible that chromatin remodeling could partly explain (or at least participate in) HRD in OC [ 58 ].…”
Section: From Ovarian Cancer Genetics To Homologous Recombination Def...mentioning
confidence: 99%
“…In eukaryotic cells, chromatin refers to a linear composite structure comprising DNA, histones, nonhistone proteins, and RNA (Kornberg and Thomas 1974). Chromatin modifiers regulate the chromatin structure by influencing the assembly, disassembly, and rearrangement of the nucleosomes on the chromatin, thereby improving the localization of the transcription factors and other transcription-related elements in the chromatin DNA (Clapier 2021;Reyes et al 2021). The chromatin structure changes dynamically in cells, and was distinct at different epigenomic states (Xu et al 2018) (Fig.…”
Section: Optical Imaging Of Chromatin Modifiersmentioning
confidence: 99%